2016
DOI: 10.1051/0004-6361/201527277
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band spectral energy distribution of 3000 Å break quasars from the Sloan Digital Sky Survey

Abstract: Context. In past decades, huge surveys have confirmed the existence of populations of exotic and hitherto unknown quasar types. The discovery and investigation of these rare peculiar objects is important because they may represent links to special evolutionary stages and hold clues to the evolution of quasars and galaxies. Aims. The Sloan Digital Sky Survey (SDSS) discovered the unusual quasars J010540.75-003313.9 and J220445.27+003141.8 and a small number of similar objects. Their spectra are characterised by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 134 publications
1
19
0
Order By: Relevance
“…Similar to our previous surveys presented in Paper I and II, we observe cases where previously parametrized extinction curves (Gordon et al 2003;Zafar et al 2015) do not reproduce the observed reddening (see also Hall et al 2002;Meusinger et al 2016). In this work, we identify 14 such cases (Sect.…”
Section: Peculiar Quasar Propertiessupporting
confidence: 88%
“…Similar to our previous surveys presented in Paper I and II, we observe cases where previously parametrized extinction curves (Gordon et al 2003;Zafar et al 2015) do not reproduce the observed reddening (see also Hall et al 2002;Meusinger et al 2016). In this work, we identify 14 such cases (Sect.…”
Section: Peculiar Quasar Propertiessupporting
confidence: 88%
“…Using strong, broad emission lines as the only indicator for quasar identification is a simple and robust way to verify that the source is indeed a quasar and simultaneously allows a determination of the redshift. However, this approach comes with one main drawback: not all quasars exhibit these broad, characteristic emission lines (Meusinger et al 2012(Meusinger et al , 2016Krogager et al 2015Krogager et al , 2016. For the main science case of the MALS project, namely the study of intervening cold gas absorption, such a bias against non-standard quasars (incl.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In total this paper presents new spectroscopic data for 11 systems. Finally, seven new candidate detached magnetic white dwarf binaries were discovered during a search for unusual quasars in Kohonen maps of SDSS spectra (Meusinger et al 2012(Meusinger et al , 2016. These systems are discussed in Section 6.…”
Section: Target Selectionmentioning
confidence: 99%